The Effectiveness of Reap (Reading, Encoding, Annotating, Pondering) Technique On Reading Comprehension - Ismail (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2019)
This research focused on reading skill. This skill was selected because it was an important, skill as a way to get information. Thus, the objective of this research was to find out whether or not the implementation of REAP (reading, encoding, annotating, pondering) technique can effective the reading comprehension of the eighth year students of SMP Negeri 5 Alla in academic year 2018/2019. The method used in this research was quasi-experimental method, that used two classes which consisted of one experimental class and one control class. The experimental class consisted of 22 students and the control class consisted of 28 students. So, the total of the sample was consisted of 50 students. The result of the data analysis shows that the students’ reading comprehension improved. It can be seen from the mean score of pre-test and post-test between experimental class and control class. The mean score of experimental class in pre-test was 66.59 and in post-test was 75.68. Meanwhile, the mean score of the control class in pre-test was 64.46 and in post-test was 68.04. It indicated that the improvement of the experimental class who got treatment through REAP technique was higher than control class who did not get treatment through REAP technique. After analyzing the data by using the t-test formula, the result of the t-test value in post-test was 2.584 and t-table value was 1.677. It means that the t-test value (2.584) was higher than t-table value (1.677). This indicates that H1 was accepted and H0 was rejected.